Development of Science Literacy Integrated Reading Materials Using a Scientific Approach on Factors Affecting Reaction Rates - Della Syaras Wati; Ayu Dwi Yulianti; Farah Erika; Pintaka Kusumaningtyas; Via Arabella Rodrigo (Phenomenon : Jurnal Pendidikan MIPA, 2025)
This research is motivated by the need to develop science literacy in the Merdeka Curriculum in response to the challenges of the Society 5.0 era, which demands collaboration between students, teachers, and technology. This study aims to design and test the validity, practicality, and effectiveness of reading materials integrated with science literacy through a scientific approach. This research follows the Research and Development (R&D) method using Sugiyono's model, involving senior high school students in East Kalimantan. The validation results by media experts, material experts, and practitioner experts were declared very valid. Practicality was assessed by teachers (95,87%) and students (82,65%), both categorized as very practical. Teacher activity observations scored 100% indicated excellent implementation, and student activity observations scored 89,5%, categorized as very good. Effectiveness was shown through an increase in N-Gain analysis resulted in a value of 4,0 (moderate category) and an Effect Size value of 1,7 (very large category). These findings indicate that the developed reading materials are effective in improving students' science literacy and can support contextualized learning relevant to technological developments and local needs.